Changes in the crystalline degree in neutron irradiated EPDM viewed through infrared spectroscopy and inelastic neutron scattering - Lambri, Osvaldo Agustin F. (2018)
The changes in the degree of crystallinity in commercial Ethylene Propylene Diene rubber-type M (EPDM) irradiated with neutrons at different doses has been studied by means of inelastic neutron scattering and infrared absorption spectroscopy experiments. EPDM samples were taken from the housing of non-ceramic electrical insulators which are used in outdoor transmission lines of 66 kV. Inelastic neutron scattering spectra were recorded at 5 K with an accessible energy-transfer range between 180 - 3500 cm-1. Infrared studies were performed at room temperature with an energy transfer between 4000 - 400 cm-1. Controlled neutron irradiation allows to obtain different volume fraction and size of crystalline zones in EPDM. The obtained results are discussed and correlated with studies of differential scanning calorimetry, dynamic mechanical analysis and positron annihilation lifetime spectroscopy from where the changes in crystallinity in EPDM were indirectly studied. Inelastic neutron scattering studies were not appropriate for determining the changes in the crystallinity degree in neutron irradiated commercial EPDM. In contrast, from infrared absorption spectroscopy the changes in crystallinity could be determined successfully.